2016
DOI: 10.3390/vaccines4020020
|View full text |Cite
|
Sign up to set email alerts
|

N. meningitidis and TLR Polymorphisms: A Fascinating Immunomodulatory Network

Abstract: N. meningitidis infections represent a global health problem that can lead to the development of serious permanent sequelae. Although the use of antibiotics and prevention via vaccination have reduced the incidence of meningococcal disease, our understanding regarding N. meningitidis pathogenesis is still limited, especially of those mechanisms responsible for IMD and fulminant or deadly septic shock. These severe clinical presentations occur in a limited number of subjects, whereas about 10% of healthy indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Arbour et al found that the individual with both TLR4 Asp299Gly and TLR4 Thr399Ile polymorphisms would be hyporesponsive when challenged with LPS and was less efficient in eliciting distinct innate immune responses [31]. The polymorphic variant of TLR4 also results in an increased susceptibility to other microbial infections, such as Toxoplasma gondii, Cytomegalovirus, Neisseria meningitides, Mycobacterium leprae and other intracellular pathogens [14,49,50]. However, further discussion about this TLR4 polymorphism association with non-Salmonella infectious diseases is not within the scope of this review.…”
Section: Host Genetic Variants 21 Toll-like Receptor 4: Initiates Tmentioning
confidence: 99%
“…Arbour et al found that the individual with both TLR4 Asp299Gly and TLR4 Thr399Ile polymorphisms would be hyporesponsive when challenged with LPS and was less efficient in eliciting distinct innate immune responses [31]. The polymorphic variant of TLR4 also results in an increased susceptibility to other microbial infections, such as Toxoplasma gondii, Cytomegalovirus, Neisseria meningitides, Mycobacterium leprae and other intracellular pathogens [14,49,50]. However, further discussion about this TLR4 polymorphism association with non-Salmonella infectious diseases is not within the scope of this review.…”
Section: Host Genetic Variants 21 Toll-like Receptor 4: Initiates Tmentioning
confidence: 99%
“…However, since the incidence of IMD is much lower than this, other factors are involved in the risk of progressing to IMD after colonisation. This fulcrum rests on the virulence of the isolate and the underlying health of the host 17,18 . Until recently, N. meningitidis was not associated with urogenital disease and was considered to be a transient asymptomatic coloniser of the urogenital compartment.…”
Section: Neisseria Spp That Act As Pathogens In the Human Hostmentioning
confidence: 99%